Analisis Kepuasan Peternak Plasma terhadap Kinerja Kemitraan Ayam Pedaging di Kabupaten Kampar Provinsi Riau - E. Irawati; D. Fitra; I. Kantra (State Islamic University of Sultan Syarif Kasim Riau, 2020)
The plasma farmer assessment of the company is very important in supporting the sustainability of the partnership relationship. The index of satisfaction is the difference between perceived performance and expectations. The purpose of this study is the evaluation and analysis of chicken business and the measurement of the Customer Satisfactory Indexs (SCI) of plasma farmers in partnership in Kampar Regency, Riau Province. This research is a descriptive study using survey research methods on plasma farmers who partner with poultry companies. It consists of 30 plasma farmers in partnership with foreign capital companies, 10 plasma farmers in partnership with multi-national companies and 6 plasma farmers in partnership with local companies, which were taken by purposive sampling design. Likert scale is used to describe the characteristics of farmers, business characteristics and variable indexes of satisfaction with company performance. The dominant characteristics of broiler partnership plasma farmers in Kampar Regency were: successful broiler farming > 4 years, have partnered for > 2 years, the reason for partnering to want a client, get sources of information directly from the partnership company, chicken farming age 35-36 days with harvest weight 1.7-1.8 kg and mortality <3%. The conclusion of this study is the Customer Satisfaction Index (CSI) of foreign capital company partnership services of 73.38% (satisfied), multi-national company partnerships of 74.08% (satisfied). While local company partnerships had a CSI of 57.66% or neutral/ ordinary criteria.